2018
DOI: 10.1080/14756366.2018.1484735
|View full text |Cite
|
Sign up to set email alerts
|

Ethenesulfonyl fluoride derivatives as telomerase inhibitors: structure-based design, SAR, and anticancer evaluation in vitro

Abstract: Based on our previous docking model, in order to carry out more rational drug design, totally 82 vinyl sulfonyl fluorides, including some 2-(hetero)arylethenesulfonyl fluorides and 1,3-dienylsulfonyl fluorides derivatives as potential human telomerase inhibitors were designed and synthesised. The in vitro anticancer activity assay showed that compound 57 (1E,3E)-4-(4-((E)-2-(fluorosulfonyl)vinyl)phenyl)buta-1,3-diene-1-sulfonyl fluoride exhibited high activity against A375 and MDA-MB-231 cell lines with IC50 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…A structure-based design study of ethenesulfonyl fluoride derivatives, including certain 2-(hetero) arylethenesulfonyl fluoride and 1,3-dienylsulfonyl fluoride derivatives, indicates another group of chemical compounds that may be used as synthetic telomerase inhibitors and by extension in anti-cancer therapy. Some of these compounds exhibit potent inhibitory activities against telomerase though interaction with hTERT, as indicated by the modified TRAP assay ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…A structure-based design study of ethenesulfonyl fluoride derivatives, including certain 2-(hetero) arylethenesulfonyl fluoride and 1,3-dienylsulfonyl fluoride derivatives, indicates another group of chemical compounds that may be used as synthetic telomerase inhibitors and by extension in anti-cancer therapy. Some of these compounds exhibit potent inhibitory activities against telomerase though interaction with hTERT, as indicated by the modified TRAP assay ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, a total of 82 ethenesulfonyl fluorides were screened as potential human telomerase inhibitors by Liu and coworkers. 61 The experimental results demonstrated that compounds 28c, 28d and 28e possess potent inhibitory activity against telomerase. A molecular docking experiment showed that the ethenesulfonyl fluoride fragment could be well aligned with the active site of hTERT ( Figure 3).…”
Section: Short Review Syn Thesismentioning
confidence: 94%
“…Among them, 3‐(3,5‐dichlorophenoxy)‐nitrostyrene ( 28 ) may inhibit hTERT via binding to a site distinct from the active site. Ethenesulfonyl fluoride derivatives containing a styrene structure showed telomerase inhibition, wherein compounds 29 , 30 , and 31 showed inhibitory activities with IC 50 of 0.71, 0.81, and 0.97 mM, respectively …”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%